PENERAPAN PSIKOEDUKASI UNTUKMENINGKATKAN PENERIMAAN DIRI WBP DI LP KELAS IIB AMUNTAI - Bagus Legowo; Dhiza Aliffia, Dina Amalia Anggraini, Fathiatul Husna, Hendri, Marnita Handayani, Najmii Aanisah, Ra (JOURNAL OF COMMUNITY DEDICATION, 2023)
Real Work Lecture is a form of community service carried out by students as a compulsory activity to apply the theory learned during lectures and applied in the field or community environment according to a predetermined period of time and in accordance with the Tridharma of Higher Education. One of the KKN work programs is self-acceptance psychoeducation. Self-acceptance is one of the positive attitudes towards oneself, where a person is able and willing to accept the state of self. The purpose of psychoeducation is to improve a person's ability to accept himself and improve his ability to deal with problems. The research in this service program uses the Participatory Action Research method. PAR is a research that involves the active participation of researchers in planning, implementing, and implementing actions taken with the aim of solving the problems at hand. The psychoeducational activities carried out not only explain self-acceptance but also how important it is for us to accept ourselves, especially when we are in a situation that has never been imagined before, namely serving a period of detention in a correctional institution.